Search for pair production of second-generation leptoquarks at s =13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2019)
A search for pair production of second-generation leptoquarks is performed using proton-proton collision data collected at ffiffi s p ¼ 13 TeV in 2016 with the CMS detector at the CERN LHC, corresponding to an integrated luminosity of 35.9 fb−1. Final states with two muons and two jets, or with one muon, two jets, and missing transverse momentum are considered. Second-generation scalar leptoquarks with masses less than 1530(1285) GeV are excluded for β ¼ 1.0ð0.5Þ, where β is the branching fraction for the decay of a leptoquark to a charged lepton and a quark. The results of the search are also interpreted as limits on the pair production of long-lived top squarks in an R-parity violating supersymmetry model that has a final state with two muons and two jets. These limits represent the most stringent limits to date on these models.